FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN E_FILLING PADA WAJIB PAJAK ORANG PRIBADI DI JAKARTA BARAT - Daryatno, Andreas Bambang (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2017)
The purpose of the research is to examine whether perceived usefulness, perceived ease of use, complexity, security and privacy, attitude toward using, readiness technology taxpayers information and voluntariness of using have significant effect on the e-filing use.  Thisresearch conducted on individual taxpayers located in West Jakarta. Total respondents were used as samples are as many as 100 people . This research uses SPSS version 23 software (Statistical Product and Service Solution 23)and Microsoft Excel inthe processing of research data. The results of this research show that perceived ease of use, complexity, security and privacy, readiness technology taxpayers information and voluntariness of using have a significant effect on the e-filing use, while attitude toward using don’t have a significant effect on e-filing use.Key words: Perceived Usefulness, Perceived Ease of Use, Complexity, Security and Privacy, Voluntariness, Readiness Technology Taxpayers Information, Tax General Knowledge, E-Filing Use